Genetic association study between T-786C NOS3 polymorphism and essential hypertension in an Algerian population of the Oran city. Issue 2 (March 2019) - Amrani-Midoun, Asma; Kiando, Soto Romuald; Treard, Cyrielle; Jeunemaitre, Xavier; Bouatia-Naji, Nabila
Abstract: Background: Essential hypertension is an important risk factor for the development of cardiovascular disease. Important candidate genes such as NOS3 gene have been widely studied and reported to be associated with essential hypertension (HTN) in human populations. Aim: We aim in this study to analyze the relationship between NOS3 -786T/C, a common genetic variant and HTN in a sample of the Algerian population of the Oran city. Methods: A case-control study has been performed in 154 subjects including 77 hypertensives and 77 normotensives. The recruitment of these subjects was done in local Health Centers of the city of Oran, West Algeria. HTN was defined as elevated systolic blood pressure SBD ≥ 140  mmHg and or sustained diastolic blood pressure DBP≥90  mmHg, measured using an Omron ® Automatic BP Monitor - M-3W machine. Consents were obtained from all participants. Polymerase chain reaction (PCR) combined with restrictive fragment length polymorphism (RFLP) was used to genotype the NOS -786T/C variant. Results: The distribution of the allelic frequencies did not differ between cases and controls (OR = 1.48; 95%CI [0.94–2.32], P = 0.09). However, after adjustment with the age, sex, and body mass index, we observed significant association between NOS -786C allele and HTN status (OR = 2.08; 95%CI [1.18–3.66], P = 0.01). Conclusion: Our results indicate that the C allele of the NOS3 gene is associated with increased risk of essential hypertension in this sample of the Algerian population of the Oran city. Further validation in larger samples is needed to confirm this finding.